Vitamin dificiencies and neural tube defects. Issue 12 (December 1976) - Smithells, R W; Sheppard, S; Schorah, C J
Abstract : Serum folate, red cell folate, white blood cell vitamin C, riboflavin saturation index, and serum vitamin A were determined during the first trimester of pregnancy in over 900 cases. For each of these there was a social classes I + II showed the highest levels which differed significantly from other classes, except for serum folate. In 6 mothers who gave birth to infants with neural tube defects, first trimester serum folate, red cell folate, white blood cell vitamin C, and riboflavin values were lower than in controls. In spite of small numbers the differences were significant for red cell folate (P less than 0-001) and white blood cell vitamin C (P less than 0-05). These findings are compatible with the hypothesis that nutritional deficiencies are significant in the causation of congenital defects of the neural tube in man.